Predictable returns in an emerging stock market: Evidence from Qatar - Hesham I. Almujamed (Taylor & Francis Group, 2018)
This article investigates the performance of moving-average strategies and tests the validity of the weak form of the Efficient Market Hypothesis (EMH) for the Qatari Stock Exchange (QSE). This study uses statistical analyses and adopts the version of the variable moving-average rule where buy and sell signals are generated by comparing a share price’s short- and long-term moving averages. The data include the daily closing share prices of 44 Qatari-listed companies for the period 2004–2017. The analysis shows that the QSE is not weak form efficient because patterns and trends are present in share prices. Sectoral analyses suggest that securities in consumer goods and services, industrials and insurance are the most efficiently priced on the QSE. The evidence suggests that profitability depends on the moving-average strategy selected. The findings may thus benefit technical analysts, fund managers, accountants and academics. This study is one of the first to examine the market efficiency of the QSE using trading rules. This research also suggests the possibility of limited transparency and accounting disclosure in the QSE, which may help policy-makers devise regulations that could improve the QSE’s efficiency.